Near-target and other heavy residues in the interaction of ¹²C and ¹⁶O with ¹⁰³Rh - Buthelezi, Edith Zinhle (Stellenbosch : University of Stellenbosch, 2011)
Dissertation (PhD)--University of Stellenbosch, 2004.